Fundos de investimento em ações no Brasil: performance e expertise de gestão - Castro, Artur Eduardo da Nave e (2012)
This article analyzes the Brazilian stock mutual funds market, proposing dynamic rankings constructed from different risk-return performance metrics during the period from 1998 to 2009. We can evidence an unusual level of persistence, especially among the funds with better performance due to the expertise of managers. The quarterly rebalancing of portfolios based on these rankings allows us to infer that in scenarios characterized by economic boom, the equal weighted strategies in funds winners provide significant increases in average monthly earnings, risk reduction associated with diversification and consequent increase in performance in relation to market or sectoral benchmarks. This evidence is robust to the use of different performance metrics for the selection of funds, signaling that the shareholders of the winner funds require good performance not only in Sharpe, but also on other metrics, such as Treynor, Sortino and Calmar. In these optimistic scenarios, only the index of the industrial sector (INDX) provided values compatible with these portfolios of funds. However, in crisis scenarios, no strategy involving the funds can provide the levels characteristic of the hedging index of the electricity sector (IEE). It is possible to show that the majority of these strategies are dominated by the benchmarks on the riskreturn criteria, except for the value weighted portfolios composed by looser funds, a sign that the common shareholders of the big and passive funds may be experiencing higher levels of inertia.